The promotion effect of FeS2 on Sb2S3 bioleaching and Sb speciation transformation - Zheng, Xing-fu; Xia, Jin-lan; Nie, Zhen-yuan; Cao, Hong-peng; Hu, Rui-Jia; Liang, Yu-ting; Liu, Hong-chang (Frontiers in Microbiology, 2025)
Stibnite (Sb2S3) is an important but difficult to biologically leach mineral, so it is important to find a potential scheme for improving the bioleaching rate of Sb2S3. In this study, by combining experiments and first-principles density functional theory (DFT) calculations, the impact and related mechanisms of pyrite (FeS2) on stibnite (Sb2S3) bioleaching were studied for the first time. The bioleaching results revealed that FeS2 obviously improved the Sb2S3 bioleaching rate, and in the 0.5FeS2:0.5CuFeS2 system, the bioleaching rate of Sb2S3 increased from 2.23 to 24.6%, which was the best mass mixing ratio. The XPS and XANES results revealed that during the bioleaching process, Sb2S3 was transformed to Sb2O3 and Sb2O5. The electrochemical results revealed that after FeS2 was mixed, a FeS2-Sb2S3 galvanic cell formed, which promoted the electron transfer efficiency and redox reaction of Sb2S3. The DFT results show that between the Sb2S3 (0 1 0) and FeS2 (1 0 0) surfaces, S-Fe, S-S, S-Sb, and Sb-Fe bonds are formed, and the direction of electron transfer is from Sb2S3 to FeS2; the work functions for Sb2S3 after addition of FeS2 decrease, implying that faster electron transfer occurs; Fe(III)-6H2O derived from FeS2 adsorbs on the surface more easily than does glucose, which is the major component of the extracellular polymeric substances in bacteria, indicating that during the bioleaching process, Fe(III)-6H2O plays an important role; after mixing, both Fe(III)-6H2O and glucose adsorb on the Sb2S3 (0 1 0) surface more easily, with stronger bonds and larger adsorption energies, which are in good agreement with the experimental results.